Immune-related adverse events and neutrophil-to-lymphocyte ratio as prognostic indicators in gynecologic cancer patients receiving pembrolizumab: a real-world analysis - Kao, Chien-Hsiang; Lin, Hao; Ou, Yu-Che; Fu, Hung-Chun; Tsai, Ching-Chou; Wu, Chen-Hsuan (Frontiers in Immunology, 2026)
ObjectiveTo investigate whether immune-related adverse events and pretreatment neutrophil-to-lymphocyte ratio can serve as predictive biomarkers of treatment response and survival in patients with gynecologic cancer receiving pembrolizumab immunotherapy.MethodsThis retrospective study included 94 patients with gynecologic malignancies treated with pembrolizumab at Kaohsiung Chang Gung Memorial Hospital between May 2017 and July 2024. Detailed clinical and laboratory data including the occurrence of immune-related adverse events, pretreatment neutrophil-to-lymphocyte ratio, mismatch repair (MMR) status, treatment response patterns, and patient demographics were collected. Progression-free survival and overall survival were analyzed using Kaplan-Meier curves and Cox regression models. The optimal neutrophil-to-lymphocyte ratio cut-off value for predicting the prognosis was determined using receiver operating characteristic curve analysis.ResultsOverall, immune-related adverse events occurred in 55.3% of the patients and were associated with a significantly higher objective response rate (ORR; 84.6% vs. 15.4%, p < 0.001), longer progression-free survival (p < 0.001), and improved overall survival (p < 0.001). Similarly, low neutrophil-to-lymphocyte ratio (<4.07) also predicted longer progression-free survival (HR: 0.537, p = 0.043) and improved overall survival (HR: 0.328, p = 0.001). Multivariate analysis confirmed that both immune-related adverse events and low neutrophil-to-lymphocyte ratio were robust independent predictors of progression-free survival and overall survival. MMR-deficient tumors were associated with a significantly higher ORR (60.9% vs. 28.9%, p = 0.011), although MMR status was not independently associated with survival in the final multivariate models.ConclusionThe development of immune-related adverse events and low pretreatment neutrophil-to-lymphocyte ratio independently predicted improved therapeutic response and prolonged survival in gynecologic cancer patients treated with pembrolizumab. Their integration with tumor molecular profiling may optimize monitoring frequency, adjust supportive care measures, and consider treatment modifications based on individual patient risk profiles, thereby enhancing the delivery of immunotherapy in gynecologic cancers without limiting treatment access.